Case report: Refractory intestinal Behçet’s syndrome successfully treated with tofacitinib: A report of four cases - Zhao, Na; Tang, Yanchun; Wang, Shaokun; Cui, Liping; Sun, Xuehui; Wang, Zhihua; Liu, Ying (Frontiers in Immunology, 2022)
Behçet’s syndrome (BS) is a chronic form of relapsing multisystem vasculitis, characterized by recurrent oral and genital ulcers. Intestinal BS is a special type of BS. Volcano-shaped ulcers in the ileocecum are a typical finding of intestinal BS, and punched-out ulcers can be observed in the intestine or esophagus. At present, there is no recognized radical treatment for intestinal BS. Glucocorticoids and immunosuppressants are currently the main drugs used to improve the condition. Although it has been reported that monoclonal anti-TNF antibodies may be effective for some refractory intestinal BS, further randomized, prospective trials are necessary to confirm these findings. Some patients are restricted from using biological agents because of serious allergic reactions of drugs, inconvenient drug injections or the impact of the novel coronavirus epidemic. If endoscopic remission (endoscopic healing) is not achieved for a prolonged period of time, serious complications, such as perforation, fistula formation, and gastrointestinal bleeding can be induced. Therefore, it is necessary to develop new treatment methods for controlling disease progression. We reviewed the relevant literature, combined with the analysis of the correlation between the pathogenesis of BS and the mechanism of Janus kinase (JAK) inhibition, and considered that tofacitinib (TOF) may be effective for managing refractory intestinal BS. We report for the first time that four patients with severe refractory intestinal BS were successfully treated with TOF. We hope to provide valuable information on JAK inhibitors as potential therapeutic targets for the treatment of severe refractory intestinal BS.